KUALIFIKASI AKADEMIK DAN KOMPETENSI GURU MATEMATIKA DI MADRASAH ALIYAH SALAHUDDIN NANGALILI - Ryan Nizar Zulfikar (Institut Agama Islam Darul Ulum Kandangan, 2019)
This study aims to determine the academic qualifications and competencies of mathematics teachers at Madrasah Aliyah Salahuddin Nangalili. The method used in this research is qualitative method. The data analysis used was document analysis, documentation and interview interview analysis. The results of the study show that there is a mismatch of mathematics teacher academic qualifications with educational background which influences the learning process. This also affects the four mathematics teacher competencies in the form of pedagogic, professional, social and personal. Pedagogic competence is carried out with the limited ability of the teacher as well as the professional ability to prepare theoretical knowledge carried out tend to be one-way. Adapting academic qualifications and increasing teacher competency cannot be implemented due to lack of educators and remote school locations.